Hubungan Ekuitas Merek, Pemasaran Digital dan Penetapan Harga terhadap Strategi Peningkatan Minat Beli - Ghifar Ulwan; Hapzi Ali (PT. Hasba Edukasi Mandiri, 2025)
The relationship between brand equity, digital marketing, and pricing on strategy to increase buying interest is a scientific article in the literature study within the scope of the field of Strategic Management. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals. The results of this article: 1) Brand equity has an effect on strategy to increase buying interest; 2) Digital marketing has an effect on strategy to increase buying interest and 3) Pricing has an effect on strategy to increase buying interest.